Effect of boron supplementation on plasma element distribution in ovariectomized rats subjected to acute swimming exercise - Yazici, Z.; Baltaci, A.K.; Mogulkoc, R.; Halifeoglu, I.; Kaya, Y. (My University, 2011)
Background: This study aims to examine how boron supplementation affects distribution of elements in the plasma of rats whose ovaries were removed and who were subjected to swimming exercise. Methods: The study included 80 Sprague-Dawley type female rats, which were equally allocated to 8 groups. Group 1: General control, Group 2: Exercise control; Group 3: Ovariectomized control, Group 4: Ovariectomized exercise, Group 5: IP (intraperitoneal) boron-supplemented control, Group 6: IP boron-supplemented exercise, Group 7: Ovariectomized, IP boron-supplemented exercise, group 8: Ovariectomized, IP boron-supplemented. Following the exercise, blood samples were collected from all animals by decapitation, and analyzed in terms of plasma copper, iron, phosphorus, magnesium, calcium, and zinc using an atomic absorption spectrophotometer. Results: Groups 1 and 5 had the lowest copper (p<0.01) and the highest zinc and calcium (p<0.01) levels, in comparison to other groups. Phosphorus levels in groups 3, 5 and 8 were significantly lower than those in other groups (p<0.01). Magnesium levels in groups 3, 5 and 8 were higher, relative to the levels in other groups (p<0.01). Conclusion: Results of the study indicate that acute swimming exercise in ovariectomized rats supplemented with boron leads to significant modifications in the distribution of some trace elements in the plasma. It can be emphasized as a separate result of this study that changes in copper, zinc and calcium levels were independent of boron supplementation.
Keywords: Boron supplementation; Elements; Minerals; Ovariectomy; Rat